Pengaruh Komunikasi Internal dan Pengembangan Karir terhadap Retensi Pegawai Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu Provinsi Sulawesi Selatan - Muhammad Jaslin; Muh. Ichwan Musa; Agung Widhi Kurniawan; Zainal Ruma; Khaidir Syahrul (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2025)
Businesses and organizations frequently struggle with staff retention. At the Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu Provinsi Sulawesi Selatan, the goal of this study is to determine how career development and internal communication impact employee retention. Using the basic random selection technique, 45 people were chosen as a sample from the 83 government employees that make up the research population. After distributing surveys to gather data, IBM SPSS software was used for a number of statistical analyses. It was discovered that internal communication and career development had a positive and considerable effect on employee retention, both separately and in combination. Internal communication is rated at 1.381, while career development is rated at 0.825. The results of the study show that staff retention at the Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu Provinsi Sulawesi Selatan is impacted by internal communication and career development.